Background Characteristics and Cognitive Factors as Determinants of Oral Health in Pregnant Women, Tehran, Iran: A Cross-Sectional Study - Mina Shirmohammadi; Simin Zahra Mohebbi; Samane Razeghi; Mohammad Reza Khami; Ahmad Reza Shamshiri; Hoda Bahramian (Tehran University of Medical Sciences, 2024)
Objectives: Pregnancy can lead to oral health issues, yet many women remain unaware of the potential negative impact on their pregnancy. This study aimed to assess the dental and periodontal health of pregnant women in Tehran, Iran, and identify its associated factors. Materials and Methods: A cross-sectional study was conducted with 221 pregnant women attending 12 randomly selected public health centers in Tehran, Iran. A self-administered questionnaire gathered data on background characteristics, oral health knowledge, and self-reported health. Periodontal status, oral hygiene, and dental health were assessed using bleeding on probing (BOP), simplified oral health (OHI-S), and decayed-missing-filled teeth (DMFT) indices. Statistical analysis included simple and multiple linear regression (P<0.05). Results: The participants' ages ranged from 18 to 42 years (mean: 27.9 years, SD: 5.5). On average, participants scored 4.1 out of 11 (SD: 1.7) for general oral health knowledge and 1.62 out of 4 (SD: 0.9) for knowledge about oral health during pregnancy. The mean DMFT was 8.28 (SD: 5.7), with 65.6% of women having fair oral hygiene according to the OHI-S. Participants reporting poor general health had more debris (B: 0.276, P=0.043), while those with higher general oral health knowledge had fewer missing teeth (B: -0.183, P=0.048). Conclusion: Despite partial free oral health care provided to pregnant women in Iran, the dental and periodontal conditions of the participants were unsatisfactory. Implementing motivational educational programs within the primary health care system could be instrumental in improving the oral health of pregnant mothers.